Effect of Honey (Apis dorsata [Hymenoptera: Apidae]) on Larval Growth and Silk Cocoon Yield of Bombyx mori (Lepidoptera: Bombycidae). Issue 6 (25th November 2019) - Bhatti, Muhammad Farooq; Azizullah,; Shahzadi, Naila; Tahir, Hafiz Muhammad; Ali, Shaukat; Zahid, Muhammad Tariq; Khurshid, Rizwan
Abstract: The present study was carried out to determine the influence of 2% aqueous honey ( Apis dorsata Fabricius, 1793 [Hymenoptera: Apidae]) on larval growth and silk cocoon yield of fifth-instar larvae of the silkworm, Bombyx mori (Linnaeus, 1758) (Lepidoptera: Bombycidae). The larvae of silkworms ( Chinese HUAKAND2 ) were divided into a control and an experimental groups ( n = 20 in each group). Control group was fed with plain mulberry leaves throughout the fifth instar, whereas the experimental group was offered mulberry leaves dipped in 2% aqueous solution of honey every other day for 4 d (days 1, 3, 5, and 7). On the other days (days 2, 4, 6, and 8), plain mulberry leaves were offered to larvae. Results showed that the average weight gain in larvae of the experimental group was 348.23 and 204.54% in case of the control group. Uneaten mulberry leaves were weighed; the control group left 34.05% of their leaves and the treated group 28.54%. The cocoon formation in the honey-treated larvae was more uniform in shape than the control group. Furthermore, honey-treated larvae began to form cocoons 7.8 ± 0.23 h earlier than the control group. We also recorded an increase of 15.34% in average weight of cocoons of the experimental group when compared with the control. Average shell percentage of fresh silk cocoons of the control and experimental groups was 20.5 and 23.5%, respectively. It is concluded from the study that 2% aqueous honey has positive impact on the larval growth and cocoon yield of B. mori .